Influence of gellan gum-hydroxyapatite spongy-like hydrogels on human osteoblasts under long-term osteogenic differentiation conditions - Bastos, Ana Raquel Fernandes (2021)
The scientific community has been doing significant efforts towards engineering new 3D bone models in recent years. Osteocytes are mechanosensitive cells that play significant roles in the maintenance of bone homeostasis. Currently, as far as we know, there are no 3D models that faithfully recapitulate a bone microenvironment capable of promoting the differentiation of osteoblasts towards osteocytes. Besides, in the existing models, the use of human cells does not prevail over the animal cell lines. For so, we propose a 3D model that may have important implications for ongoing efforts towards a better understanding of bone physiology and disease. The main aim of the current work was the promotion of an effective differentiation of osteoblasts into osteocytes by mean of using a 3D model composed of primary human osteoblasts (hOBs) cultured on Gellan Gum-Hydroxyapatite (GG-HAp) matrix under a long-term osteogenic culture. The results revealed that GG-HAp matrix stimulated a fast cell migration/entrapment, attachment, spreading, and mineralization. Moreover, the transition process from osteoblasts to osteocytes was confirmed by the expression of the osteogenic-related (ALP, Runx2, COL I, OC, OPN and OSX) and osteocyte-related (hPDPN) marker throughout the culture time. Overall, the developed 3D model holds a great promise for the treatment of various bone diseases, namely on diagnostic applications and for bone regeneration purposes.